Amiloidosi, il Percorso Diagnostico. Quando Pensarci e Come Trovarla - Silvia Farsetti; Anna Maria Ciciani; Giuseppe Curciarello; Egrina Dervishi; Santi Nigrelli; Franco Bergesio (AboutScience Srl, 2017)
Abstract non disponibile